Silver embellished PANI/CNT nanocomposite for antimicrobial activity and sequestration of dye based on RSM modelling. Issue 23 (14th October 2020) - Kumar, Vinit; Saharan, Priya; Sharma, Ashok K.; Kaushal, Indu; Dhuan, Surender
ABSTRACT: Silver doped PANI/CNT (Ag-PANI/CNT) nanocomposite was synthesized and investigated as adsorbent for its possible application in the elimination of organic dye Brilliant Blue G (BBG). The morphological characteristics of Ag-PANI/CNT were studied using Fourier transform infrared, scanning electron microscopy, elemental mapping, transmission electron microscopy and X-ray diffraction. The response of operational parameters given as adsorbent dosage, concentration, pH and contact time for dye removal were investigated by using Response Surface Methodology (RSM). The results from RSM suggested that the efficiency of BBG elimination is 98.7 under the optimum conditions of experimental factors. The adsorption studies showed that the equilibrium data fitted well with Langmuir isotherm model compared to Freundlich. Finally, the antimicrobial activities of Ag-PANI/CNT were tested against bacterial strain Escherichia coli and Salmonella typhi and fungal strains Aspergillus niger . GRAPHICAL ABSTRACT: UF0001